2018
DOI: 10.1111/oik.05122
|View full text |Cite
|
Sign up to set email alerts
|

Is sexual organ reciprocity related to legitimate pollen deposition in distylous Pulmonaria (Boraginaceae)?

Abstract: Heterostyly, i.e. the reciprocal positioning of anthers and stigmas, is a floral polymorphism that is thought to promote disassortative (i.e. between‐morph) pollination and to maintain genetic diversity within populations. Recent research, however, has shown several cases of heterostylous plant species in which the reciprocal positioning of the sexual organs varies, which may affect the likelihood of ‘legitimate’ pollination between compatible morphs, and hence morph fitness and ultimately the stability of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 35 publications
7
30
2
Order By: Relevance
“…In the distylous genus Pulmonaria , Jacquemyn et al () recently calculated inaccuracy values for a large number of populations over nine species across Europe, and documented mean 2 ‐standardized total inaccuracy values that usually varied between 4 and 11. Only in the case of an Estonian population of Pulmonaria obscura , an inaccuracy value >20 was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the distylous genus Pulmonaria , Jacquemyn et al () recently calculated inaccuracy values for a large number of populations over nine species across Europe, and documented mean 2 ‐standardized total inaccuracy values that usually varied between 4 and 11. Only in the case of an Estonian population of Pulmonaria obscura , an inaccuracy value >20 was observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a third species ( P. veris ), a strikingly different pattern was observed with total inaccuracy and imprecision being affected by high and low organs to similar extents (Armbruster et al, ). Detailed assessment of pollen deposition patterns on stigmas of Pulmonaria further showed that the percentage of legitimate pollen deposition significantly decreased with increasing individual inaccuracy, suggesting that deviations from perfect reciprocal herkogamy may be much more common in heterostylous plant species than previously assumed and have a significant impact on pollen transfer patterns (Jacquemyn et al, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Members of Pulmonaria tend to lack prezygotic barriers to mating as they have strong overlapping distributions, share pollinators (mostly bumblebees and other bees), and many produce hybrids (Meeus, Jansens, Helsen, & Jacquemyn, ; Sauer, ). Consequently, species delimitation within Pulmonaria has proven to be problematic (Bolliger, ; Meeus et al., ), as these species are morphologically similar with all having pinkish‐blue, actinomorphic, tube‐shaped flowers (Jacquemyn, Gielen, & Brys, ) and hairy leaves. In fact, Darwin () considered many Pulmonaria taxa as varieties of the same species.…”
Section: Introductionmentioning
confidence: 99%
“…In distylous plants, the reciprocal position of anthers and stigmas is the main characteristics that promote the disassortative pollination among morphs and limit selfing and sexual interference Keller et al 2014;Jacquemyn et al 2015). Variations in the inaccuracies of organs cause deviations in the level of reciprocal position and can lead to ineffective pollen flow and pollen limitation, which can affect the reproductive production in one or both morphs types (Faivre and McDade, 2001;Jacquemyn et al 2015;Jacquemyn et al 2018). Since all the populations studied are typically distylous, any change of the reproductive organs positions would result in collapse and a possible breakdown in the system.…”
Section: Inaccuracy Correlationmentioning
confidence: 99%